5z-7=7z-3z

Simple and best practice solution for 5z-7=7z-3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-7=7z-3z equation:


Simplifying
5z + -7 = 7z + -3z

Reorder the terms:
-7 + 5z = 7z + -3z

Combine like terms: 7z + -3z = 4z
-7 + 5z = 4z

Solving
-7 + 5z = 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
-7 + 5z + -4z = 4z + -4z

Combine like terms: 5z + -4z = 1z
-7 + 1z = 4z + -4z

Combine like terms: 4z + -4z = 0
-7 + 1z = 0

Add '7' to each side of the equation.
-7 + 7 + 1z = 0 + 7

Combine like terms: -7 + 7 = 0
0 + 1z = 0 + 7
1z = 0 + 7

Combine like terms: 0 + 7 = 7
1z = 7

Divide each side by '1'.
z = 7

Simplifying
z = 7

See similar equations:

| -8-9=3x+5+2x | | 1/2(5x+9)=7x | | 10=6x-7 | | 7-5z=32 | | -8(2t-(4-7))= | | (3y+2)dx-(5x-7)dy=0 | | 15x+-10=-9x+2 | | -9x-9y=0 | | 1=0.4x-0.6x-17 | | 4x+3x-6-6=10+3 | | 3x^2=3-4x | | -3n+5n=38 | | x=2500-5x | | 3.5-h=42 | | w=y(r+A) | | 3.5+42=h | | 14k-5=65 | | z+9=126 | | 183/5+29/28-11/28 | | 5+105(2d-1)=.5 | | 6s-14=-6s+5 | | 8+11t-5=6t+66-4t | | 3.5+h=42 | | -8x-x+5=-6+5-3x | | T^3+12t^2-2t-24=0 | | 3x-121 | | Y-12=3x | | 4+-2p=6 | | 3/2x-6x=1/4x+4 | | 7z+9z=128 | | 4+2x=-32 | | x-1=0,25x+x |

Equations solver categories